2021
DOI: 10.3389/fmars.2020.608021
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Effects of Climate Change on the Occurrence of the Toxic Dinoflagellate Alexandrium catenella Along Canada’s East Coast

Abstract: Alexandrium catenella produces paralytic shellfish toxins that affect marine fisheries and aquaculture as well as ecosystem and human health worldwide. This harmful algal species is extremely sensitive to environmental conditions and potentially to future climate change. Using a generalized additive mixed model (GAMM) we studied the potential effects of changing salinity and temperatures on A. catenella bloom (≥1000 cells L–1) occurrence along Canada’s East Coast throughout the 21st century. Our GAMM was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
(127 reference statements)
1
10
0
Order By: Relevance
“…GAMs are empirical-statistical models, that establish relationships between a dependent response variable and multiple predictors (independent variables; Wood, 2017). Since GAMs do not assume a particular type of response function, allowing both non-linear and linear relationships, they are considered a flexible, computing cost-effective modeling approach for assessing the responses of plankton communities (e.g., Irwin and Finkel, 2008;Llope et al, 2009;Otto et al, 2014), specifically HABs (e.g., Matus-Hernández et al, 2019;Ajani et al, 2020;Boivin-Rioux et al, 2021, to environmental factors. The basic GAM model structure can be defined as follows (Eq.…”
Section: Generalized Additive Modelsmentioning
confidence: 99%
“…GAMs are empirical-statistical models, that establish relationships between a dependent response variable and multiple predictors (independent variables; Wood, 2017). Since GAMs do not assume a particular type of response function, allowing both non-linear and linear relationships, they are considered a flexible, computing cost-effective modeling approach for assessing the responses of plankton communities (e.g., Irwin and Finkel, 2008;Llope et al, 2009;Otto et al, 2014), specifically HABs (e.g., Matus-Hernández et al, 2019;Ajani et al, 2020;Boivin-Rioux et al, 2021, to environmental factors. The basic GAM model structure can be defined as follows (Eq.…”
Section: Generalized Additive Modelsmentioning
confidence: 99%
“…Since only about 4% of its land is arable, Canada relies heavily on agrochemicals, including P fertilizers, to maintain its elevated level of food production (Malaj et al., 2020). Yet the excess P discharged into the environment has caused serious eutrophication in Canada's rivers and lakes (Boivin‐Rioux et al., 2021; Bunting et al., 2016; Seewer, 2015). Environment Canada (2011) indicated that from 2005 to 2007, 32% of surface water quality monitoring sites in Canada exceeded P guidelines more than half the time.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both temperature (Clements et al, 2018;Clements et al, 2021) and salinity are reported to affect valve gaping behaviour in bivalves but with more of closures contrary to our results who shown less of closure. However, A. catenella development in the Lower St. Lawrence Estuary is also associated with these physico-chemical parameters, in particular salinity and water temperature (Fauchot et al, 2005;Navarro et al, 2006;Aguilera-Belmonte et al, 2013;Starr et al, 2017;Boivin-Rioux et al, 2021). The optimal temperature for the development of this algae is ≈14°C (Boivin-Rioux et al, 2021), a temperature only present during summer in the St. Lawrence Estuary.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was conducted over three days at 18°C, an intermediate temperature between the optima for mussels (20°C; Almada-Villela et al, 1982) and 14°C for A. catenella (Boivin-Rioux et al, 2021). Following the 30-day acclimatation period (as described above), 24 mussels were connected to valvometry monitoring systems described in Nagai et al (2006) and Comeau (2014) (see Section 2.5 below for details).…”
Section: Experiments 1: Laboratory Experimentsmentioning
confidence: 99%
See 1 more Smart Citation